SINTESIS BARIUM M-HEKSAFERIT DENGAN DOPING LOGAM Zn MENGGUNAKAN METODE KOPRESIPITASI - Ilham Halik; Aris Doyan; Aliefman Hakim (Jurnal Penelitian Pendidikan IPA, 2016)
The aims of this study to synthesis barium M-heksaferit doped metal Zn. Synthesis of BaM using coprecipitation method by varying the concentrate of dopan 0,0; 0,3; 0,6; dan 0,9 and varying the calcinations temperature 80, 400, 600 dan 800 oC. The basic material used of Barium Carbonat (BaCO3), Iron (III) Cloride Hexahydrate (FeCl3.6H2O) ZnCl2 dan NH4OH. Synthesis process conducted at the Faculty of Mathematics and Natural Sciences Analytical Laboratories Unram. The final product of synthesis is varied colored powder light brown to dark depending on the dopan concentrate and calcinations temperature. It is found that the dark of sample increase with increase in dopan concentrate and the dark of sample increase with increase in calcinations temperature too, it is showed the product BaM can be used to softmagneticKeyword: Barium M-Hexaferrites, synthesis, coprecipitasi